ANALISIS PEMEROLEHAN FONOLOGI ANAK USIA 3 TAHUN 2 BULAN: STUDI KASUS LONGITUDINAL DALAM PERSPEKTIF PSIKOLINGUISTIK - Ridha Hasnul Ulya; Anjely Putri Nadira; Abdilla Abel Mandev; Egi Tioza Asda; Khairunas; Miftahul Hasanah; Nadiya Putri; Zaskia Fira Setya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the patterns of phonological acquisition in a child aged 3 years and 2 months whose first language is Minangkabau and who is exposed to Indonesian, as well as to map the micro-level trajectory of phonological development. Using an exploratory sequential mixed-methods design, data were collected through intensive naturalistic observation over a one-month period employing the participant observation technique, resulting in 41 spontaneous utterances that were rigorously validated through triangulation by linguistic experts. Quantitative analysis included the frequency distribution of phonological processes and the calculation of Mean Length of Utterance (MLU), while qualitative analysis interpreted speech patterns through the frameworks of developmental psycholinguistics and markedness theory. The findings revealed the dominance of substitution processes (64.71%), followed by deletion (33.33%) and cluster reduction (1.96%). Systematic patterns were identified, including /k/ → /w/, /r/ → /l/ or /w/, vowel substitution /e/ → /u/, and coda consonant deletion. An MLU score of 3.46 morphemes confirmed a level of morphological complexity consistent with developmental norms for children aged 3;0–3;6 years. The study concludes that phonological variability is adaptive in nature and reflects temporary articulatory strategies. Theoretically, the findings reinforce the validity of bilingual phonological integration within the framework of Dynamic Systems Theory. Practically, this study provides a crucial clinical baseline for speech-language pathology in distinguishing normative development from articulation disorders, while also recommending active monitoring and recasting strategies in early childhood education.